Participación del ácido hialurónico en enfermedad trofoblástica gestacional - Mascaró, Marilina (2015)
Gestational trophoblastic disease (GTD) comprises a heterogeneous group of entities related to trophoblast as complete hydatidiform mole (CHM), choriocarcinoma (CC) and placental site trophoblastic tumor (PSTT). Hyaluronic acid (HA) is the main glycosaminglycan in the extracellular matrix. CD44 and RHAMM are the main receptors to which HA interact and modulate biological processes in cancer. The aim of this Thesis project was to study the role of HA in GTD pathophysiology. We demonstrated a differential expression pattern of HA, CD44 and RHAMM in trophoblast populations from CHM, CC and PSTT. Using human choriocarcinoma cell line JEG-3 as in vitro model, we demonstrated that HA induce a biochemical differentiation to extravillous phenotype. Also HA was able to induce cell migration. Such effect was dependent of endogenous hCG level. Besides, HA-induced migration involved an elevated ERK activation dependent of PI3K and was mediated by the receptor RHAMM. This Thesis represent an important contribution into the HA field research. The relevance of knowledge of dialogue between stroma and this tumor associates with the chance to develop new therapeutic strategies in those cases with recurrent and chemoresistance disease.